Legal Strategy for Sustainable Sargassum Management to Improve the Maritime Economic of Bima - Didik Irawansah; Kasmar Kasmar; Muhamad Amin; Absori Absori (Fakultas Hukum Universitas Muhammadiyah Sorong, 2026)
The aim of this study is to describe the economic potential of Sargassum in supporting the maritime economy of coastal communities in Bima Regency and to conceptualize strategic legal policies for the sustainable management of Sargassum to enhance the economic competitiveness of coastal villages in Bima. The method used is an empirical legal study employing a mixed-methods approach, combining qualitative and quantitative methods. The study was conducted in the coastal village of Teluk Waworada, Bima Regency, using purposive sampling of relevant stakeholders. Data were collected through observation, interviews, questionnaires, and documentation. Analysis was conducted qualitatively through data reduction, presentation, and drawing of conclusions. The novelty of this study lies in the formulation of a legal governance policy model for Sargassum that has not been previously researched, integrating environmental protection, the empowerment of coastal communities, and the enhancement of maritime economic competitiveness in Bima Regency. The results of the study indicate that Sargassum makes a tangible contribution to the income and economic resilience of coastal households; however, its utilization remains traditional, lacking downstream processing and legal certainty. The conclusion is that comprehensive local regulations are needed to ensure sustainability, added value, and the competitiveness of the Sargassum-based maritime economy.